Revolutionizing accessibility: an IoT-powered doorbell for the deaf community - Wahid, Nurul Atina; Abu Bakar, Zahari; Kadiran, Kamaru Adzha; Mokhtar, Siti Musliha Ajmal (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The IoT-Powered Doorbell for the Deaf Community is a groundbreaking assistive technology solution to address communication barriers individuals with hearing impairments face. This system integrates advanced IoT technologies, including the ESP32-CAM, HC-SR04 ultrasonic sensor, LEDs, a vibration motor, and the Blynk application, to deliver a multisensory notification mechanism. Upon detecting a visitor within 100 cm, the system triggers visual alerts through LEDs, tactile feedback via vibration, and real-time smartphone notifications via the Blynk IoT app. Additionally, the ESP32-CAM enables live video monitoring for enhanced security. By prioritizing simplicity, cost-effectiveness, and accessibility, this innovation empowers deaf individuals with greater autonomy while fostering inclusivity and enhancing their quality of life.